An Empirical Study of Employee Retention in the Information Technology Sector in Bangalore City - N Krishnamoorthy; Ambreen Aisha (PT FORMOSA CENDEKIA GLOBAL, 2022)
Employee retention refers to the ability of an organization to retain its employees. Each research investigation is expected to make a definitive contribution to the existing literature. The contribution of this study would be providing some gap-filling information in the field of Employees attrition and retention in service industry in general and IT Sector in particular. Satisfaction of employees is a major problem and due to this reason service sector have high switching level of jobs. Though, companies are investing a lot on the HR practices to improve attrition rate it is suggested to think from the point of view of the employees. Present study were the employees of the IT sector; especially software engineers of various IT companies in Bangalore city. Respondents were selected randomly. Employees were mainly from TCS, Tech Mahindra, Honeywell, Caterpillar, IBM. The information of this research will be useful to service industry in their HR practices and add new information to literature. It will help the management of the IT Sector to develop their new strategies of retention. The study found the influence of HR policies, compensation and benefits, work pressure and relationship with the superiors on employee retention.